Enhancing Village-level Inventory Management through Extreme Programming: A Case Study in Rural Empowerment - Denny Jean Cross Sihombing (Jurnal Info Sains : Informatika dan Sains, 2023)
This research discusses analyzing and developing a village office inventory system using the Extreme Programming (XP) method. Village inventory systems are considered an essential foundation in local resource management, facilitating the recording, maintenance, and management of inventory owned by a village. This research identified limitations in the manual approach, which is prone to recording errors and data loss. The proposed village inventory system is designed to solve these limitations by emphasizing timeliness and accuracy of information. The system is expected to assist the village in responding quickly to changing conditions and needs, ensuring that the information obtained is always relevant and accurate. The application development was conducted through a series of XP stages, from overall planning system and module design to testing and implementation in a production environment. This process creates adaptive, responsive, and quality software, overcoming the limitations of manual systems that may still be dominant in many villages. User acceptance analysis highlights the importance of understanding user needs and expectations. User needs studies, user personas, prototyping, and feedback collection form the basis of system design that focuses on meeting user expectations. The results of the user performance metrics analysis showed a positive 80% satisfaction rate with the prototype, indicating that the proposed solution met the expectations of most users.